(Semi)hydrogenation of enoates and alkynes effected by a versatile, particulate copper catalyst - Samuel Redl; Christoph Topf (Tetrahedron Chem)
We communicate a versatile and user-friendly Cu-based catalytic method that allows for the selective hydrogenation of enoates and alkynes. The introduced protocol is free from any ex ante modifications of the used Cu(I) precursors by air-sensitive phosphines or elaborate N-heterocyclic carbene ligands. The conjugate hydrogenation of enoates and the (selective) reduction of C≡C bonds is achieved through a [Cu(CH3CN)4]+/tert-butoxide pair whereby we describe a delicate influence of the base cation on the chemoselectivity of the respective transformation. In case of the ester-to-alcohol reduction, a combination of simple CuI and NaOtBu proved to be successful. Deuteration experiments are included to address certain mechanistic aspects of the introduced catalytic system. All requisite chemicals are readily obtainable through commercial channels and the catalyst assembly is set up on the bench without the need for special lab-technical precautions.